Medical Education in Somalia: Navigating Issues and Challenges Amid the COVID-19 Epidemic - Dahie , Hassan Abdullahi (Advanced Concepts in Medicine and Medical Research Vol. 9, 2023)
This chapter is intended to identify the issues and challenges of medical education in Somalia. Improving medical education has been aspirational aim for the countries around the world over the past century to realize the universal health coverage. Through the continuous endeavors of the world countries and their learning institutions, tremendous advances have taken place in the field of medical education over the last five decades. However, being a low-resource and fragile country afflicted by protracted social conflicts and political fragmentation, Somalia faced difficulties in establishing its medical education institutions. Therefore, the study was conducted in Medical Universities & Colleges in Somalia between February to April 2021 using a cross-sectional study design and 384 individuals were selected for this study. An author-developed questionnaire and interview guide was utilized as data collection tools. The questionnaire was designed for the teaching staff who were involved in medical teaching and learning process to address the demographic characteristics, education qualifications, teaching strategies employed of the facilitators, while the interview guide was developed for medical education managers and policy makers to identify administrative challenges in medical education. The respondents of the study were selected through purposive sampling. The collected quantitative and qualitative data were analyzed using SPSS and NVIVO software packages, respectively. A descriptive analysis was undertaken using frequency and percentages for the categorical variables with SPSS version 25.0 while thematic analysis was employed with NVIVO version 12 for non-categorical qualitative variables. Results: In the sample of 384 participants, 311 males and 73 females were included in the study with mean age 33 years. Most of them had master’s degree and average teaching experience of 5 years. Majority of medicine and health sciences institutions were private-owned operating in rented campuses. The study revealed a significant correlation between the type of institution, staff employment type, student selection policy, ownership of the campus, and employee satisfaction with current salary. On the other hand, it was also found that the medical education in Somalia faces some major challenges including shortage of trained competent lecturers, lack of relevant medical curricula, shortage of teaching/learning resources, lack of government oversight & licensing and lack of higher education policies. Therefore, it is concluded that Somalia needs to incorporate a competency-based curriculum, improve the availability of teaching and learning resources, provide training to medical teachers on teaching approaches, and increase investment in research in this field.